Two-Dimensional Haeckelite NbS2: A Diamagnetic High-Mobility Semiconductor with Nb4+ Ions - Ma, Yandong; Kuc, Agnieszka; Jing, Yu; Philipsen, Pier; Heine, Thomas (Angewandte Chemie International Edition, 2017)
In all known Group 5 transition-metal dichalcogenide monolayers (MLs), the metal centers carry a spin, and their ground-state phases are either metallic or semiconducting with indirect band gaps. Here, on grounds of first-principles calculations, we report that the Haeckelite polytypes 1S-NbX2 (X=S, Se, Te) are diamagnetic direct-band-gap semiconductors even though the Nb atoms are in the 4+ oxidation state. In contrast, 1S-VX2 MLs are antiferromagnetically coupled indirect-band-gap semiconductors. The 1S phases are thermodynamically and dynamically stable but of slightly higher energy than their 1H and 1T ML counterparts. 1S-NbX2 MLs are excellent candidates for optoelectronic applications owing to their small band gaps (between 0.5 and 1 eV). Moreover, 1S-NbS2 shows a particularly high hole mobility of 2.68×103 cm2 V−1 s−1, which is significantly higher than that of MoS2 and comparable to that of WSe2.
CRIS-Team Scopus Importer:2022-04-14
Keywords: carrier mobility; diamagnetic materials; semiconductors; transition-metal dichalcogenides; two-dimensional materials